Analysis of Road Safety Strategies in Africa: A Closer Look at the Results through the Moroccan Case Study - ASRAOUI, Otman; EL MASTOUR, Rachid; EL BAKKOUCHI, Mounir (Revue du contrôle, de la comptabilité et de l’audit, 2024)
Road accidents pose an enduring threat to lives, property, and infrastructure in Africa, challenging countries, societies, and economies despite numerous strategies and governance plans. Alarming and rising accident rates across African nations necessitate preventive actions, including revisiting strategies and fortifying institutional frameworks. Analyzing this issue involved extracting an African model and examining its strategies, challenges, and stakes. Morocco serves as a case study due to its extensive efforts in attaining road safety, highlighting both successes and failures, alongside existing constraints. Identifying shortcomings enables proposing initial steps toward ensuring road safety, a pivotal factor in achieving desired outcomes.